Enzalutamide-Resistant Progression of Castration-Resistant Prostate Cancer Is Driven via the JAK2/STAT1-Dependent Pathway - Luo, Yong; Yang, Xiaobing; Basourakos, Spyridon P.; Zuo, Xuemei; Wei, Dechao; Zhao, Jiahui; Li, Mingchuan; Li, Qiankun; Feng, Tao; Guo, Pengju; Jiang, Yongguang (Frontiers in Molecular Biosciences, 2021)
Previous studies have shown that CXCR7 expression is up-regulated after enzalutamide (ENZ) treatment and increased level of CXCR7 could increase the invasion, migration and angiogenesis of castration-resistant prostate cancer (CRPC) cells. We now demonstrate that the levels of p-JAK2, p-STAT1, C-Myc and VEGFR2 were significantly reduced after CCX771, a specific CXCR7 inhibitor, treatment. And this effect was further increased after combination treatment of ENZ and CCX771. Then we verified targeting inhibition of JAK2 or STAT1 could remarkably increase apoptosis and DNA damage, and decrease migration of CRPC cells. More importantly, the combination treatment group of ENZ plus JAK2/STAT1 inhibition led to much greater suppression than single inhibition group of JAK2 or STAT1. Subcutaneous CRPC xenograft tumor growth was also reduced by single ENZ treatment and single FLUD, a specific STAT1 antagonist, treatment; but much superior effect was elicited by the combination treatment of ENZ+FLUD. Proliferative indices in tumor tissues were significantly decreased following combination treatment compared with control-treatment tissues and single agent treatment tissues. Our results demonstrate that CXCR7, which indicates an AR-independent signal pathway, could put forward CRPC progression via downstream JAK2/STAT1 signal transduction cascade. Combined inhibition targeting both AR and JAK2/STAT1 resulted in substantially tumor suppression due to reduction in DNA damage repair ability and increment in apoptosis.